Product Spatial Sequence Modeling based on Spatial State Transition Petri net of Behavior Flow - Hao Yongtao; Zou Zhaoguo; Lou Diming (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
FBS model proposed three levels of abstraction (function, behavior, structure) and eight design stages used to describe the design. The model becomes the basis of many computer-aided design practices. In this paper, based on FBS model, behavior flow ontology conception is proposed, and the conception can describe the dynamic and continuous of behavior of products more accurately .The behavior flow mechanism extends to structure layer too. Spatial sequence is the exhibition of behavior flow in the structure layer. This paper analyzes the relationship between behavior flow and spatial sequence, and the relationship between spatial sequence and function. A model to express the spatial sequence of behavior flow is proposed, by dividing spatial sequence into two parts, spatial connection relation of product and spatial state transition process. Spatial connection relation is the description of the product composition, expressed by spatial semantic network; the spatial state transition process of behavior flow is the process to realize the function, expressed by spatial state transition Petri net of behavior flow. Spatial sequence of behavior flow of engine is represented by this model as an example. Finally, a conceptual design framework based on behavior flow is proposed as the further research direction. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3310